Measurement of J/ψ production in association with a W± boson with pp data at 8 TeV - Alconada Verzini, María Josefina (2020)
A measurement of the production of a prompt J/ψ meson in association with a W± boson with W± → µν and J/ψ → µ +µ − is presented for J/ψ transverse momenta in the range 8.5–150 GeV and rapidity |yJ/ψ| < 2.1 using ATLAS data recorded in 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of √ s = 8 TeV and correspond to an integrated luminosity of 20.3 fb−1 . The ratio of the prompt J/ψ plus W± cross-section to the inclusive W± cross-section is presented as a differential measurement as a function of J/ψ transverse momenta and compared with theoretical predictions using different double-parton-scattering cross-sections.